ANALISIS ASPEK MORAL DALAM NOVEL INCEST KARYA I WAYAN ARTIKA - Trisna Lesmana, I Komang Harry (Humanis; Volume 5. No. 2. November 2013, 2014)
This article analyzed the moral aspect in a novel entitled Incest written by I Wayan Artika in which it is literal sociology study. The problems analyzed in this study included how the moral of the characters in society and the influence of the characters towards the community in the novel. The background of analyzing this novel was due to the existence of societal aspect in the novel and to elaborate how the novel itself and also how the writer describe the traditional values which are related to ‘kembar buncing’ in a modern life. The result from the analysis showed that Incest is an illustration of human’s way of thinking which still focusing on the old tradition and showed the effect of things done in community. The methodology used in this article, firstly, was done by obtaining data using reading technique, listen and take note towards the resources. And then followed by describing the facts found in the field and analyzed it deeper. The discussion part talked about the good characters of Geo dan Bulan who wanted to built up the village to recover. Differ from the manners of the grandfather from Nyoman Sika who showed bad manner, for example, stealing things from the Temple which caused the grandchildren from that old man was born ‘kembar buncing’.
Keywords: moral positive and negative, consequence from attitude, novel Incest.